Nature-inspired optimisation methods: the ant algorithm. (2008)
Nature has inspired many optimization techniques/ methods. This paper is directed to introduce some of these methods to the reader and emphasis was laid on the ant algorithm by discussing its properties and what it entails. Also some of the problems that ant algorism has been used to solve was listed while two of them were discussed in full,the TSP which the writer worked on and network routing